FUNDAMENTALS OF VOCAL AND CHORAL WORK DURING TEACHING OF STUDENTS OF SINGING (Pedagogy of Higher and Secondary Education, 2003)
On a present day stage of development of musical pedagogics the problem of forming of vocal-choral skills in the process of pupils’ education is the most actual. The vocal-choral singing takes a special place in the aesthetical and artistic pupils' upbringing. The purpose of music lessons in the secondary school is upbringing of pupils' musical culture. One of the most important tasks that a modern lesson of music solves is to teach children singing.
Keywords: vocal-choral work; process o f teaching pupils